BYLAWS OF TOBACCO INDUSTRY LABOR/MANAGEMENT COMMITTEE (AN UNINCORPORATED NON-PROFIT ASSOCIATION) (Tufts Archival Research Center, 2007)
Duplicate; Copy; Bylaws of the Tobacco Institute Labor Management Committee (LMC). Includes voting procedures, mission, membership requirements, financial procedures, and officers.